DDDR-20. TARGETING THE SELECTIVE VULNERABILITY OF IDH-MUTANT GLIOMA WITH ZOTIRACICLIB. (14th November 2022) - Pang, Ying; Yu, Guangyang; Ranjan, Alice; Wang, Herui; Sergi, Zach; Kim, Olga; Merchant, Mythili; Zhang, Meili; Song, Hua; Zhang, Wei; Davis, Dionne; Gilbert, Mark; et al.
Abstract: BACKGROUND: IDH mutations are common in diffuse gliomas and confer an increased dependency on oxidative mitochondrial function. Zotiraciclib, a multi-kinase inhibitor, not only suppresses CDK9-mediated gene transcription process but also causes mitochondrial dysfunction in preclinical models. We investigated the selective activity of zotiraciclib in IDH-mutant gliomas. METHODS: Cytotoxicity of zotiraciclib was determined in patient-derived glioma cells with/without IDH mutations. Immunoblotting and flow cytometry were used to evaluate the cell death pathways. Real-time ATP production was measured by Seahorse assay. RESULTS: The EC50 of zotiraciclib in IDH-wt cells was twice as high as in IDH-mutant cells. In low-dose zotiraciclib (15nM)-treated IDH-mutant cells, RNA Pol II phosphorylation and expression of antiapoptotic proteins, including XIAP, MCL-1 and survivin were decreased significantly. Cleaved caspase 3/7, 8, 9 and LC3B were also detected in treated IDH-mutant cells but not in IDH-wt cells, suggesting activation of intrinsic and extrinsic cell apoptosis pathways, and subsequent autophagy of IDH-mutant cells. Low-dose treated IDH-mutant, but not IDH-wt cells, induced decreased expression of a panel of mitochondrial respiration genes, and mitochondrial respiration complexes, cellular ATP depletion and increased ROS production, suggesting a greater disruption of mitochondrial function in zotiraciclib-treated IDH-mutant cells. Zotiraciclib treatment prolonged the survival in mice bearing intracranial IDH-mutant gliomas (30 days in DMSO-treated group vs 33 days in zotiraciclib-treated group, p = 0.01), but not in mice with glioma established with the isogenic IDH-wt glioma cells (18 days in DMSO-treated vs 20 days in zotiraciclib-treated group, p = 0.10). CONCLUSIONS: There is selective activity of zotiraciclib in IDH-mutated glioma. Low-dose exposure of zotiraciclib induces cell death and suppresses transcriptional process and mitochondrial biogenesis in IDH-mutant glioma, not in IDH-wt tumors. These findings support a clinical trial testing zotiraciclib in IDH-mutated glioma. The treatment efficacy seen even at low concentrations further supports testing it as a single agent, thereby reducing toxicity concerns.